Going beyond the waterfall : managing scope effectively across the project life cycle - Davis, Barbara, 1969-; Radford, Darren, 1972- (J. Ross Publishing, 2014)
This book will help project teams understand how and when scope changes and evolves as a part of a living-development process by answering the ultimate question: "Are we doing the right things the right way?" Key features covered: defines scope from program management to business case and requirements; identifies how scope evolves and what causes it to change; illustrates how stakeholder engagement, requirements, and project and enterprise architecture methodologies impact scope and management; demonstrates the implications of change management and implementation on scope throughout the development and roll-out processes; discusses the evolution of scope as a key process in the achievement of project objectives; and explains the definition and management process of scope from concept to implementation. -- Edited summary from book.
Keywords: Project management.; Business planning.; elektronické knihy; electronic books